Keanekaragaman Jenis Ikan Rawa di Kecamatan Upau Kabupaten Tabalong - Almira Ulimaz (Bioscientist : Jurnal Ilmiah Biologi, 2020)
South Kalimantan is the most densely populated province on the island of Borneo. The province which consists of two main geographical features is also rich in natural resources and a diversity of agroecosystems. Apart from the provincial capital, Banjarmasin, other regencies still have abundant nuftah plasma, including the biological wealth in the form of fish. One of the districts that still has natural resources in the form of fish is Tabalong Regency. As a district which is also famous for its abundant mining products in the form of coal and petroleum, of course animal resources in the form of fish are quite valuable assets to be preserved. Therefore, a research was conducted which aims to identify and explain the types of fish that live in the Swamp, Upau District, Tabalong Regency. The method used in this research is the method of observation which is analyzed descriptively. The sample in this study were fish caught by fishing line and nets. The activity using fishing rods is carried out for 30 minutes, and with nets it is carried out 5 tosses at each point at the sampling station. The number of species found was 142 fish consisting of 10 species, 3 orders, and 8 families. The orders found included the orders Perciformes, Cypriiformes, and Siluriformes. The families found included Cyprinidae (Cypriiformes), Channidae, Belontiidae, Anabantidae, Cichlidae (Perciformes), Bagridae, Siluridae, and Claridae (Siluriformes). The index of fish species diversity in Rawa, Upau District, Tabalong Regency is in the "Medium" category, namely 1.987.